2011
DOI: 10.1007/s12012-011-9107-1
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Ameliorates Vascular Endothelial and Contractile Dysfunction in the Thoracic Aorta of Diabetic Rats

Abstract: Studies have shown that tetracycline class antibiotics exhibit an ameliorating action with its antioxidant property on increased oxidative stress in tissues, including heart. Since endothelial vascular dysfunction in diabetes is associated with increased oxidative stress and prevented with antioxidants, herein, we aimed to test a hypothesis whether a low-dose doxycycline treatment of diabetic rats for 4 weeks can ameliorate endothelial vascular dysfunction of thoracic aortas. Results of the present study shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
(137 reference statements)
2
27
0
Order By: Relevance
“…Furthermore, total protein-thiol level was not affected by either diabetes or NAC treatment (data not shown). We, therefore, demonstrated that there is marked increase in oxidative stress in the heart of diabetics besides a high circulatory level of lipid peroxidation [32] from STZ-induced diabetic rat, and it can be controlled to normal level by NAC treatment, which is confirmed also with previously published data [3335]. …”
Section: Resultssupporting
confidence: 88%
“…Furthermore, total protein-thiol level was not affected by either diabetes or NAC treatment (data not shown). We, therefore, demonstrated that there is marked increase in oxidative stress in the heart of diabetics besides a high circulatory level of lipid peroxidation [32] from STZ-induced diabetic rat, and it can be controlled to normal level by NAC treatment, which is confirmed also with previously published data [3335]. …”
Section: Resultssupporting
confidence: 88%
“…Acetylcholine (ACh) and sodium nitroprusside-induced vasorelaxation were studied on isolated rat aortas. Oxidative stress indices such as SOD, CAT, LPO and NO levels were determined in rat aortas at end of the treatments[1617]. …”
Section: In Vivo Experimental Methodmentioning
confidence: 99%
“…This was attributed to an inhibition of eNOS function due to cav-1 binding and a reduction of NO production [189, 190]. …”
Section: Endothelial Dysfunctionmentioning
confidence: 99%